Hospitality Management Competence - Raras, Pungky Nanda; Oktaria, Eka Travilta; A.A, Iskandar; Barusman, Andala Rama Putra; Habiburahman, Habiburahman (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The growth and changes facing the hotel industry globally have in several ways affected the competence of its personnel. There is growing concern about graduate competency and what industry requires. Previous studies reveal that hospitality management programs do not adequately prepare hospitality students with the competencies necessary to fit today's workplace. Therefore, educational institutions must play their role in developing and instilling important competencies in their graduates so as to prepare them for the competitive world of work. This paper aims to investigate the competencies required by hospitality graduates from an industry perspective. This paper is based on previous studies regarding hospitality management competencies by considering competencies from the management competency model and generic skills framework. The Delphi technique was used to investigate graduate competencies from the perspective of the hospitality industry.